2016
DOI: 10.15407/ujpe61.03.0187
|View full text |Cite
|
Sign up to set email alerts
|

On the Classical Maxwell–Lorentz Electrodynamics, the Electron Inertia Problem, and the Feynman Proper Time Paradigm

Abstract: The Maxwell electromagnetic and the Lorentz type force equations are derived in the framework of the R. Feynman proper time paradigm and the related vacuum field theory approach. The electron inertia problem is analyzed within the Lagrangian and Hamiltonian formalisms and the related pressure-energy compensation principle. The modified Abraham-Lorentz damping radiation force is derived, the electromagnetic elctron mass origin is argued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The latter are completely non-relativistic and based on the canonical quantization scheme [7,71] in the case of the Coulomb gauge condition. Inspired by these and related classical results, we have shown that the quantum mechanism of self-interaction of a charged particle with its self-generated electromagnetic field consists of two physically different phenomena, whose influence on the structure of the resulting Hamilton interaction operator appears to be crucial and gives rise [64] to a modified analysis of the related classical shell model of a charged particle within the Lagrangian formalism. As a result of our scrutiny of studying the classical electromagnetic mass problem, there was demonstrated that it can be satisfactorily solved within the classical H. Lorentz and M. Abraham arguments augmented with the additional electron stability condition, which was not taken before into account yet and appeared to be very important for balancing the related electromagnetic field and mechanical electron momenta.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The latter are completely non-relativistic and based on the canonical quantization scheme [7,71] in the case of the Coulomb gauge condition. Inspired by these and related classical results, we have shown that the quantum mechanism of self-interaction of a charged particle with its self-generated electromagnetic field consists of two physically different phenomena, whose influence on the structure of the resulting Hamilton interaction operator appears to be crucial and gives rise [64] to a modified analysis of the related classical shell model of a charged particle within the Lagrangian formalism. As a result of our scrutiny of studying the classical electromagnetic mass problem, there was demonstrated that it can be satisfactorily solved within the classical H. Lorentz and M. Abraham arguments augmented with the additional electron stability condition, which was not taken before into account yet and appeared to be very important for balancing the related electromagnetic field and mechanical electron momenta.…”
Section: Introductionmentioning
confidence: 77%
“…As was shown in [64], the consequences formulated above subject to the quantum fermionic-bosonic selfinteracting phenomenon appear to be very important from the classical point of view, especially for the physical comprehension of the inertial properties of a charged particle under the action of the self-generated electromagnetic field.…”
Section: The Transformed Fock Space Its Lorentz-type Reduction and Tmentioning
confidence: 96%
See 2 more Smart Citations
“…for all k ∈ E 3 , contradicting the relationships, following from the evolution equations (38). As the latter relationships should be vanishing in the Fock space, it was suggested [12] to reduce the Fock space Φ to a subspace, on which there are satisfied the weak operator constraints (41).…”
Section: The Photon Field Dressed Electron Energy Spectrum Problemmentioning
confidence: 99%